The Legal Pluralism Dilemma in Ulayat Land Certification: The Crisis of Communal Ownership in Minangkabau - Hospi Burda; Rahmad Hidayat; Fitri Yenti; Hamdanil Hamdanil; Zul Atril (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2025)
This article aims to conceptually analyze the dilemma of legal pluralism in the implementation of land certification policies and their impact on the existence of ulayat (communal) land in Minangkabau, which has historically been communal, matrilineally inherited, and governed through a customary legal system. Amid the state’s agrarian legal modernization, a significant research gap remains concerning how certification policies—centered on individualized land ownership—affect the communal ownership structure, social function of customary law, and the spiritual values of indigenous communities. This research employs a library-based method with an interdisciplinary approach, combining perspectives from customary law, national agrarian law, and Islamic law, specifically through the lenses of legal pluralism and maqâṣid al-syarîʿah. The findings indicate that certifying ulayat land under individual ownership not only weakens the authority of ninik mamak (customary leaders) as custodians of communal land but also degrades customary identity and accelerates the fragmentation of ownership into private holdings. Furthermore, no established legal model has been found capable of safeguarding communal land rights within Indonesia's current legal system. This study offers a responsive and contextual legal harmonization framework by integrating customary law recognition into land administration mechanisms and reinforcing the principle of al-milkiyyah al-musytarakah within the maqâṣid al-syarîʿah paradigm to preserve ulayat land amidst growing agrarian liberalization.Artikel ini bertujuan untuk menganalisis secara konseptual dilema pluralisme hukum yang muncul dalam implementasi kebijakan sertifikasi tanah terhadap eksistensi tanah ulayat Minangkabau yang secara historis bersifat komunal, diwariskan secara matrilineal, dan diatur melalui sistem hukum adat. Di tengah upaya modernisasi hukum agraria nasional, masih terdapat kesenjangan kajian terkait bagaimana kebijakan sertifikasi yang berorientasi pada individualisasi hak berdampak terhadap struktur kepemilikan kolektif, fungsi sosial adat, dan nilai-nilai spiritualitas masyarakat adat. Penelitian ini merupakan studi kepustakaan (library research) dengan pendekatan interdisipliner, menggabungkan perspektif hukum adat, hukum agraria nasional, dan hukum Islam, khususnya melalui lensa teori pluralisme hukum dan maqâṣid al-syarîʿah. Hasil kajian menunjukkan bahwa sertifikasi tanah ulayat atas nama individu tidak hanya melemahkan kewenangan ninik mamak sebagai pengelola tanah komunal, tetapi juga berpotensi mendegradasi identitas adat dan mempercepat fragmentasi kepemilikan yang bersifat privat. Selain itu, ditemukan bahwa tidak terdapat model hukum baku yang mampu menjamin keberlanjutan hak komunal dalam sistem hukum nasional. Artikel ini menawarkan sebuah formulasi harmonisasi hukum yang responsif dan kontekstual melalui integrasi pengakuan hukum adat dalam administrasi pertanahan, serta penguatan nilai al-milkiyyah al-musytarakah dalam kerangka maqâṣid al-syarîʿah, untuk menjaga keberlangsungan tanah ulayat di tengah liberalisasi agraria.